Fabrication of Co3O4/NiCo2O4 Nanocomposite for Detection of H2O2 and Dopamine - Tianjiao Liu (MDPI AG, 2021)
Herein, the Co3O4/NiCo2O4 nanocomposite has been prepared as a novel electrochemical sensor to accurately detect hydrogen peroxide (H2O2) and glucose. ZIF-67 is a metal-organic framework (MOF) with Co as the center metal ion. Co3O4 can be obtained by calcination of ZIF-67 at 700 °C, which can retain the structure of ZIF-67. The hollow Co3O4 nanocrystal was synthesized based on a calcination process of ZIF-67. This open structure can promote the whole Co3O4/NiCo2O4 nanocomposite larger accessible surface area and reactive sites. Co3O4 has good electrocatalytic performance, which has been applied in many fields. Moreover, H2O2 and dopamine sensing tests indicate that the as-prepared non-enzymatic electrochemical biosensor has good detection properties. The testing results indicate the as-prepared biosensor has a wide detection range, low detection limit, high selectivity, and long-term stability. These testing results suggest the potential application in food security, biomedicine, environmental detection, and pharmaceutical analysis.